La planificación documental en la gestión municipal; el archivo de oficina - Ros García, Juan; Luján Ortega, María (Revista General de Información y Documentación, 2006)
The present article aims to show the current state of archival management of in a way general office, inside the context of the organization of the municipal taxes. And in concrete the system of information proposed in the management of tributes of the City Hall is evaluated of Murcia. The Administration currently should cover the needs of the user that by the advance of the new technologies and of the development of the company of the information, wants a fast solution al problem that presents. Therefore it is spoken of a file that is modulated according to the needs of the citizens and of the specific activities to the administration. This vision of the file of office is found very far away of the conception that has of a municipal or historic file that arrange their funds al personal investigator.
Keywords: Archival management; Information system; Administration municipal; Retrieval information; Records management